2023
DOI: 10.1145/3567592
|View full text |Cite
|
Sign up to set email alerts
|

Neural Machine Translation for Low-resource Languages: A Survey

Abstract: Neural Machine Translation (NMT) has seen a tremendous spurt of growth in the last twenty years and has already entered a mature phase. While considered the most widely used solution for Machine Translation, its performance on low-resource language pairs remains sub-optimal compared to the high-resource counterparts due to the unavailability of large parallel corpora. Therefore, the implementation of NMT techniques for low-resource language pairs has been receiving the spotlight recently, thus leading to subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Language and communication have been essential for people to get along and work together since the dawn of human civilization [1]. So, translating between different cultures has been very important to the growth of society, both economically and culturally [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Language and communication have been essential for people to get along and work together since the dawn of human civilization [1]. So, translating between different cultures has been very important to the growth of society, both economically and culturally [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, different methods were created to address the MT problem, with statistical machine translation (SMT) being one of the most well-known. However, the performance of the SMT system was largely impacted by the number of parallel sentence pairs available for training, and strong emphasis was placed on creating parallel datasets in addition to research on new MT methods [6]. The advancement of SMT systems was a turning point for many language pairs and made the task of machine translation more achievable [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, pre-trained language models (PLMs) with external semantic knowledge have shown excellent performance on many natural language processing (NLP) tasks, including named entity recognition [1]- [4], relation extraction [5]- [8], and machine translation [9]- [12]. However, traditional approaches of introducing knowledge are mostly training from scratch, which is time-consuming and computationally expensive, making it infeasible for most users.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances by neural machine translation (NMT) (Vaswani et al, 2013; Luong, Pham, and Manning, 2015; Lin et al, 2021) have shown impressive results. In addition, NMT survey studies by Wang et al (2021) and Ranathunga et al (2021) suggest that though there is the scope of improvements in NMT systems, development of tools and resources for low-resourced languages (LRLs) (Koehn and Knowles, 2017) have greatly improved. In this study, we leverage advances in NMT to automatically translate labelled user-generated content within the cyberbullying domain from Italian into English language – specifically the dataset by Sprugnoli et al (2018).…”
Section: Introductionmentioning
confidence: 99%